Rhabdomyosarcoma Cells Produce Their Own Extracellular Matrix With Minimal Involvement of Cancer-Associated Fibroblasts: A Preliminary Study - D’Agostino, Stefania; Tombolan, Lucia; Saggioro, Mattia; Frasson, Chiara; Rampazzo, Elena; Pellegrini, Stefania; Favaretto, Francesca; Biz, Carlo; Ruggieri, Pietro; Gamba, Piergiorgio; Bonvini, Paolo; Aveic, Sanja; et al. (Frontiers in Oncology, 2021)
Background The interplay between neoplastic cells and surrounding extracellular matrix (ECM) is one of the determinant elements for cancer growth. The remodeling of the ECM by cancer-associated fibroblasts (CAFs) shapes tumor microenvironment by depositing and digesting ECM proteins, hence promoting tumor growth and invasion. While for epithelial tumors CAFs are well characterized, little is known about the stroma composition of mesenchymal cancers, such as in rhabdomyosarcoma (RMS), the most common soft tissue sarcoma during childhood and adolescence. The aim of this work is to identify the importance of CAFs in specifying RMS microenvironment and the role of these stromal cells in RMS growth. Methods We assessed in two dimensional (2D) and three dimensional (3D) systems the attraction between RMS cells and fibroblasts using epithelial colon cancer cell line as control. CAFs were studied in a xenogeneic mouse model of both tumor types and characterized in terms of fibroblast activation protein (FAP), mouse PDGFR expression, metalloproteases activation, and ECM gene and protein expression profiling. Results In 2D model, the rate of interaction between stromal and malignant cells was significantly lower in RMS with respect to colon cancer. Particularly, in 3D system, RMS spheroids tended to dismantle the compact aggregate when grown on the layer of stromal cells. In vivo, despite the well-formed tumor mass, murine CAFs were found in low percentage in RMS xenogeneic samples. Conclusions Our findings support the evidence that, differently from epithelial cancers, RMS cells are directly involved in their own ECM remodeling, and less dependent on CAFs support for cancer cell growth.